Flavonoids as Potential Anti-Inflammatory Molecules: A Review - Al-Khayri, Jameel M.; Sahana, Gandasi Ravikumar; Nagella, Praveen; Joseph, Biljo V.; Alessa, Fatima M.; Al-Mssallem, Muneera Q. (Molecules (Basel, Switzerland), 2022)
Hydroxylated polyphenols, also called flavonoids, are richly present in vegetables, fruits, cereals, nuts, herbs, seeds, stems, and flowers of numerous plants. They possess numerous medicinal properties such as antioxidant, anti-cancer, anti-microbial, neuroprotective, and anti-inflammation. Studies show that flavonoids activate antioxidant pathways that render an anti-inflammatory effect. They inhibit the secretions of enzymes such as lysozymes and β-glucuronidase and inhibit the secretion of arachidonic acid, which reduces inflammatory reactions. Flavonoids such as quercetin, genistein, apigenin, kaempferol, and epigallocatechin 3-gallate modulate the expression and activation of a cytokine such as interleukin-1beta (IL-1β), Tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and interleukin-8 (IL-8); regulate the gene expression of many pro-inflammatory molecules such s nuclear factor kappa-light chain enhancer of activated B cells (NF-κB), activator protein-1 (AP-1), intercellular adhesion molecule-1 (ICAM), vascular cell adhesion molecule-1 (VCAM), and E-selectins; and also inhibits inducible nitric oxide (NO) synthase, cyclooxygenase-2, and lipoxygenase, which are pro-inflammatory enzymes. Understanding the anti-inflammatory action of flavonoids provides better treatment options, including coronavirus disease 2019 (COVID-19)-induced inflammation, inflammatory bowel disease, obstructive pulmonary disorder, arthritis, Alzheimer’s disease, cardiovascular disease, atherosclerosis, and cancer. This review highlights the sources, biochemical activities, and role of flavonoids in enhancing human health.